Update breast cancer 2022: Part 4 - Advanced-stage breast cancer = Update Mammakarzinom 2022 : Teil 4 - Brustkrebs in fortgeschrittenen Krankheitsstadien - Aktaş, Bahriye; Fehm, Tanja; Welslau, Manfred; Müller, Volkmar; Lüftner, Diana; Schütz, Florian; Fasching, Peter A.; Janni, Wolfgang; Thomssen, Christoph; Witzel, Isabell; Belleville, Erik; Untch, Michael; et al. (Geburtshilfe und Frauenheilkunde, 2022)
For the treatment of patients with advanced HER2-negative hormone receptor-positive breast cancer, several substances have been introduced into practice in recent years. In addition, other drugs are under development. A number of studies have been published over the past year which have shown either an advantage for progression-free survival or for overall survival. This review summarizes the latest results, which have been published at current congresses or in specialist journals, and classifies them in the clinical treatment context. In particular, the importance of therapy with CDK4/6 inhibitors - trastuzumab deruxtecan, sacituzumab govitecan and capivasertib - is discussed. For trastuzumab deruxtecan, an overall survival benefit in HER2-negative breast cancer with low HER2 expression (HER2-low expression) was reported in the Destiny-Breast-04 study. Similarly, there was an overall survival benefit in the FAKTION study with capivasertib. The lack of overall survival benefit for palbociclib in the first line of therapy raises the question of clinical classification.
Gesehen am 14.02.2023